2020
DOI: 10.1097/ncc.0000000000000816
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Symptom Clusters and Functional Performance in Adult Acute Leukemia Patients Under Chemotherapy

Abstract: Background Adult acute leukemia (AL) patients who receive chemotherapy usually experience multiple symptoms during the treatment course. The symptom clusters (SCs) as well as subsets of concurrent symptoms in AL patients have not yet been demonstrated. Objective To investigate the SCs of adult AL patients who were receiving chemotherapy and to determine their correlations with functional performance. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 38 publications
(84 reference statements)
6
27
1
Order By: Relevance
“…It might be because elderly patients had better coping strategies due to more life experience than that of young patients. Furthermore, in agree with previous studies, our data suggested that more female patients reported severe symptom distress of psycological SC than the male [7,21]. At last, the distress of psychological SC was in uenced by the patients' treatment outcome.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It might be because elderly patients had better coping strategies due to more life experience than that of young patients. Furthermore, in agree with previous studies, our data suggested that more female patients reported severe symptom distress of psycological SC than the male [7,21]. At last, the distress of psychological SC was in uenced by the patients' treatment outcome.…”
Section: Discussionsupporting
confidence: 92%
“…The rst SC was psychological SC which included symptoms of feeling nervous, worrying and feeling sad. Although the speci c symptom items might be different in the cluster, psychological SC has been demonstrated as a common SC in patients with cancer, either solid tumor or hematological malignancy [5][6][7]. Speci c psychological symptom in MM had been reported in previous studies [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 23 studies included in this review, 13 used a cross-sectional design to identify symptom clusters in oncology patients receiving chemotherapy (online supplemental table 1). Seven studies were conducted in the USA,29 32–37 two in China,38 39 two in Thailand,40 41 one in Austria,42 and one in Turkey 43. Sample sizes ranged from 9641 to 1328 29.…”
Section: Resultsmentioning
confidence: 99%